Artificial Intelligence in English Language Learning: Exploring Personalised Learning for Generation Z - Shrestha, Buddi Laxmi Lakhe; Karmacharya, Rajan (SXC Journal, 2025)
This study delves into the transformative influence of artificial intelligence (AI) to enhance Generation Z students’ English language learning. In today’s digitalized setting, Gen-Z students are more accustomed to new technology, particularly AI-powered applications. The study incorporates semi-structured interviews with two language educators and two students from four different institutions in Kathmandu Valley. This study employs a qualitative interpretive research design with in-depth interviews and open-ended questions. The report also emphasises AI’s potential for generating individualised learning experiences, increasing student engagement, and identifying acquaintances in real-time evaluations. However, building on Van Dijk’s digital Divide theory, the study examines how unequal access to AI tools can impede equitable learning opportunities. The study examines the problems and limitations of incorporating AI tools into English language education, with an emphasis on Gen Z. Furthermore, this study examined accessibility challenges, teaching roles, and ethical concerns related to AI and its tools. Results from this study contribute to the future of English education by looking at how artificial intelligence is revolutionizing English language education for Generation Z students.